Cognitive Processes in Alcohol Binges: A Review and Research Agenda - Field, Matt (2008)
Alcohol abuse is associated with a cluster of long-term changes in cognitive processes, as predicted by contemporary models of addiction. In this paper we review evidence which suggests that similar changes may occur during an alcohol binge, and as such they may play an important role in explaining the loss of control over alcohol consumption that occurs during alcohol binges. As a consequence of both acute alcohol intoxication (alcohol ‘priming’ effects) and exposure to environmental alcohol-related cues, we suggest that a number of changes in cognitive processes are likely. These include increased subjective craving for alcohol, increased positive and arousing outcome expectancies and implicit associations for alcohol use, increased attentional bias for alcohol-related cues, increased action tendencies to approach alcohol, increased impulsive decision-making, and impaired inhibitory control over drives and behaviour. Potential reciprocal relationships between these different aspects of cognition during an alcohol binge are discussed. Finally, we discuss the relationship between the current model and existing models of cognitive processes in substance abuse, and we speculate on the implications of the model for the reduction binge drinking and its consequences.